KAJIAN TINGKAT KENYAMANAN PADA JALUR PEDESTRIAN DI KOTA MANADO (STUDI KASUS: JALAN SAM RATULANGI) - Hanry, Irwan; Tungka, Aristotulus; Malik, Andy M. (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
One of the important elements in urban planning efforts is the element of convenience. Creating comfortable urban spaces for residents requires the provision of adequate infrastructure and supports activities within it. Comfort is basically related to personal safety and human security in urban spaces. Pedestrian paths are one of the important elements in the urban planning process because of their role as a link and support for the important functions of urban space, especially if pedestrian roads can guarantee the safety and comfort of pedestrian users. Therefore, it is necessary to examine the comfort level of pedestrian infrastructure paths in Manado City. The analytical method used is descriptive statistical analysis method. This study refers to 4 important aspects of the comfort of pedestrian paths, namely aspects of circulation, aspects of security, aspects of cleanliness, aspects of beauty.